A [videorecording (DVD)] - Tatsuya, Mori (Facets Video, 2006)
Documents the inside activities of Japan's religious cult Aum Shinrikyo, who released sarin gas into Tokyo's subway system in 1995. Not only was the daily life captured, but also the media frenzy, vicious tactics of undercover cops, and anger of local residents who wanted to evict the cult from their community.